Kisspeptin in the Prediction of Pregnancy Complications - Tsoutsouki, Jovanna; Patel, Bijal; Comninos, Alexander N.; Dhillo, Waljit S.; Abbara, Ali (Frontiers in Endocrinology, 2022)
Kisspeptin and its receptor are central to reproductive health acting as key regulators of the reproductive endocrine axis in humans. Kisspeptin is most widely recognised as a regulator of gonadotrophin releasing hormone (GnRH) neuronal function. However, recent evidence has demonstrated that kisspeptin and its receptor also play a fundamental role during pregnancy in the regulation of placentation. Kisspeptin is abundantly expressed in syncytiotrophoblasts, and its receptor in both cyto- and syncytio-trophoblasts. Circulating levels of kisspeptin rise dramatically during healthy pregnancy, which have been proposed as having potential as a biomarker of placental function. Indeed, alterations in kisspeptin levels are associated with an increased risk of adverse maternal and foetal complications. This review summarises data evaluating kisspeptin’s role as a putative biomarker of pregnancy complications including miscarriage, ectopic pregnancy (EP), preterm birth (PTB), foetal growth restriction (FGR), hypertensive disorders of pregnancy (HDP), pre-eclampsia (PE), gestational diabetes mellitus (GDM), and gestational trophoblastic disease (GTD).